(untitled) (Global Journal of Management and Business Research, 2020)
This study aims to analyze the influence of the brand personality on consumer loyalty. Using a quantitative approach preceded by an exploratory study, a survey of 353 consumers of the Guinness brand made it possible to test and verify our different research hypotheses, using multiple linear regression analyzes. The result obtained highlights the direct influence of five brand personality traits on loyalty measured through attitude, preference and consumer engagement with the brand. It thus underlines the interest for managers to take into account the concept of brand personality in the management of their brands.